TINGKAT PENERAPAN TATA KELOLA TEKNOLOGI INFORMASI (IT GOVERNANCE) TERHADAP KUALITAS SDM BERDASARKAN MODEL PENGUKURAN COBIT: A SYSTEMATIC LITERATURE REVIEW - Andi Mahardika; Dinda Salsabila Yaswi; Kiki Fitria Damayanti; M Syahrul Alifathurrahman; Naura Salsabila Aulia Z.; Rheinata Saskya Aziizah D. (Universitas Nusa Cendana, 2023)
The increasingly advanced developments have helped human activities. There are still many companies that fail to use technology effectively. Therefore, it needs IT Governance. Effective management of information systems can be done by utilizing a framework at the agency to evaluate the domain of COBIT, one of which is Manage Human Resources (APO07). Two models are often used in research related to APO07, Capability Level and Maturity Level. This study aims to measure the effectiveness of the application of the model as an evaluation medium, especially in the field of Human Resources (APO07), so that readers can find out the level of effectiveness of the influence of the model on the progress of the agency. Thirty-six (36) articles were used to search for keywords about the influence of information technology governance in the field of human resources. In conducting this research, two selections were made. The first selection was 32 articles, and the second selection was 16 articles. From the results of the study, it can be seen that of the 16 articles, 3 of them have implemented IT Governance effectively, while the other 13 have not implemented it effectively. Keywords: IT Governance; COBI; Maturity Level; Capability Level; Human Resource